Simulation of Forced Ventilation in Closed Building As COVID-19 Precaution - Cheong, Yung Khai; Fatimah Mohamed Yusop, (Progress in Engineering Application and Technology, 2022)
Fresh air is referred as the supply of air for human which containing oxygen particles in the air. Unfortunately, the current outbreak of COVID-19 has becoming fresh air supply is needed more in closed area which would enable to neutralize the virus of COVID-19. The supply of air in the closed area basically from the HVAC system such as air-conditioning. The air movement is circulated and reused in the closed area. Ventilation system as forced ventilation can be used for more supply of fresh air in a closed area. It is usually used to control the air quality by adulterate unnecessary particles in temperature, and airflow velocity. In closed area, COVID-19 infection is easier to transmit the virus while fresh air supply insufficient. Hence, a Computational Fluid Dynamics (CFD) simulation is used to simulate the airflow and temperature in a closed area by using force ventilation to the building.